Spiritual traditions : essential visions for living : a book in honour of David C. Scott - Singh, David Emmanuel (Bangalore, Delhi, UTC/ISPCK., 1998)
Contributed essays
Keywords: India; India.-- Religious life and customs; Monastic and religious life; Monastic and religious life.-- India